Transformasi manajemen risiko pada lembaga keuangan syariah di era fintech dan ekonomi digital - Fuad, Muhammad Fajrul (Maliki Interdisciplinary Journal, 2026)
The digital transformation in the financial sector has significantly impacted Islamic financial institutions, particularly in risk management practices. This study aims to analyze the role of fintech in enhancing the effectiveness of risk management and to identify challenges faced in the digital economy era. The method used is a literature review by examining various relevant academic journals. The findings indicate that technologies such as artificial intelligence, big data, and blockchain improve risk analysis accuracy, operational efficiency, and transaction transparency. However, this transformation also introduces new risks, including cybersecurity risk, operational risk, and sharia compliance risk. Therefore, it is necessary to strengthen technology-based risk management strategies, supported by adaptive regulations and stakeholder collaboration. In conclusion, the transformation of risk management is essential to enhance the competitiveness and sustainability of Islamic financial institutions in the fintech and digital economy era.